2001
DOI: 10.1038/sj.bdj.4800942
|View full text |Cite
|
Sign up to set email alerts
|

The laser welding technique applied to the non precious dental alloys procedure and results

Abstract: RESEARCHprosthodontics have a laser in their laboratory. However, looking at the available literature, since 1970 many experiments have been conducted into non precious and precious alloys and have shown contradictory results, probably because the experimental procedures used were different. 15,16,17,18,19 Therefore no comparison could be made. In this study, the weldability of three non precious alloys was investigated. The procedure consisted of determining the appropriate welding parameters which could achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 13 publications
1
37
0
11
Order By: Relevance
“…Pulsed laser welding devices can be used to join broken parts of a Co-Cr removable partial denture with soldering wires with a composition similar to that of the Co-Cr alloy, thus eliminating the adverse effect of galvanic coupling. Nevertheless, laser welding demonstrates other advantages, combining a rapid, economic, and accurate way for joining metals and alloys 45. However, laser welding is more technique-sensitive, and the optimization of the technique requires the training of the dental technician, especially for the identification of appropriate welding conditions 46…”
Section: Properties Of Co-cr Aloys For the Production Of Rpd Frameworkmentioning
confidence: 99%
“…Pulsed laser welding devices can be used to join broken parts of a Co-Cr removable partial denture with soldering wires with a composition similar to that of the Co-Cr alloy, thus eliminating the adverse effect of galvanic coupling. Nevertheless, laser welding demonstrates other advantages, combining a rapid, economic, and accurate way for joining metals and alloys 45. However, laser welding is more technique-sensitive, and the optimization of the technique requires the training of the dental technician, especially for the identification of appropriate welding conditions 46…”
Section: Properties Of Co-cr Aloys For the Production Of Rpd Frameworkmentioning
confidence: 99%
“…Moreover, the heat source is a concentrated high-power light beam, so minimizing distortion problems in the prosthetic pieces [3]. The process allows the possibility of welding adjacent to acrylic resin or ceramic parts with neither physical (cracking) nor colour damage [4], thereby allowing a reduction of working time by eliminating the necessity to remake broken prosthetic or orthodontic appliances. …”
Section: Introductionmentioning
confidence: 99%
“…The process allows the possibility of welding in proximity to acrylic resins or ceramic parts with no physical (cracking) or colour damage [30] and these characteristics diminish the working time through the elimination of the necessity for the remaking of broken prosthetic or orthodontic appliances. Several works based on laboratory tests have concluded that laser-welded joints have a high, reproducible strength [31].…”
Section: Resultsmentioning
confidence: 99%